Strategic intensification in butanol production by exogenous amino acid supplementation: Fermentation kinetics and thermodynamic studies. (September 2019) - Nimbalkar, Pranhita R.; Khedkar, Manisha A.; Kulkarni, Rahul K.; Chavan, Prakash V.; Bankar, Sandip B.
Graphical abstract: Highlights: Exogenous addition of tryptophan:phenylalanine triggered butanol production. Amino acid addition after 8 h in batch cultivation resulted in 12.43 ± 0.1 g/L butanol. Fed-batch with in-situ product recovery was promising for improved butanol titer. ABE production follow first order kinetics with respect to intermediate concentration. Thermodynamics of ABE fermentation was studied to evaluate reaction feasibility. Abstract: Amino acids are vital precursors in many biochemical production pathways in addition to efficient nitrogen source which could enhance microbial growth yields. Therefore, in present study, the effect of amino acids from aliphatic and aromatic family was comprehensively evaluated in batch and integrated fed batch fermentation system. Clostridium acetobutylicum NRRL B-527 was able to utilize 54.15 ± 1.0 g/L glucose to produce 12.43 ± 0.10 g/L butanol under batch cultivation. Interestingly, a significant step up in butanol titer (20.82 ± 0.33 g/L) was achieved by using fed-batch fermentation process integrated with liquid–liquid extraction module. Besides, mathematical modeling studies demonstrated the best fitting of experimental data with first order reaction kinetics. Overall, an enhancement in solvent titer by induction of essential cellular components coupled with advance bioprocess strategy was successfully utilized in this study for its further applications.